Adjunctive preladenant: A placebo-controlled, dose-finding study in Japanese patients with Parkinson's disease. (November 2016) - Hattori, Nobutaka; Kikuchi, Masashi; Adachi, Noriaki; Hewitt, David; Huyck, Susan; Saito, Tadayuki
Abstract: Background: Preladenant, an adenosine 2A antagonist, reduced daily OFF time when administered as adjunctive treatment in a previous phase 2 trial in non-Japanese Parkinson's disease (PD) patients on stable doses of levodopa. This study aimed to evaluate preladenant as adjunctive therapy in Japanese patients with PD. Methods: In this randomized, placebo-controlled, double-blind, 12-week, dose-ranging, phase 2 study, Japanese patients with moderate to severe PD on a stable regimen of levodopa were randomly assigned 1:1:1:1 to preladenant 2 mg, 5 mg, or 10 mg BID or placebo. The primary efficacy end point was change from baseline to week 12 in mean OFF time, recorded using a PD diary. Safety and tolerability were also assessed. Results: In total, 111 patients were randomly assigned to receive preladenant 2 mg, and 113 each received preladenant 5 mg, 10 mg, or placebo. In contrast to previous data, preladenant in this study did not demonstrate statistically significant efficacy; the primary outcome was −0.7 h ( P = 0.0564), –0.5 h ( P = 0.1844), and −0.3 h ( P = 0.3386), respectively, for preladenant 2 mg, 5 mg, and 10 mg BID versus placebo. Overall, preladenant was well tolerated, and the frequency of adverse events appeared to be dose related. Conclusions: In this phase 2 study, preladenant used as adjunctive therapy in PD patients on stable doses of levodopa did not reduce mean OFF time; treatment was well tolerated at doses between 2 and 10 mg BID. Highlights: The adenosine 2A receptor is a target for treating Parkinson's disease (PD). Preladenant is a potent and selective adenosine 2A receptor antagonist. We evaluated preladenant in Japanese PD patients when given as adjunct to L-dopa. Preladenant was not effective in reducing mean OFF time after 12 weeks.